Stability of Posttreatment Reductions in World Health Organization (WHO) Drinking Risk Levels and Posttreatment Functioning in Older Adults with DSM‐5 Alcohol Use Disorder: Secondary Data Analysis of the Elderly Study. (3rd March 2021) - Mejldal, Anna; Andersen, Kjeld; Behrendt, Silke; Bilberg, Randi; Bogenschutz, Michael; Braun‐Michl, Barbara; Bühringer, Gerhard; Søgaard Nielsen, Anette
Abstract : Background: Studies have found that reductions in World Health Organization (WHO) drinking risk levels may be a stable outcome of treatment for alcohol use disorder (AUD) and associated with functional improvements. The aim of this study was to investigate whether posttreatment reductions in WHO drinking risk levels are stable over time among older adults and associated with a decrease in consequences of drinking and AUD symptoms and improved quality of life. Methods: Participants . Individuals 60+ years old, suffering from DSM‐5 AUD ( n  = 693), and seeking outpatient treatment. Measurements . WHO drinking risk levels, prior to treatment and at all follow‐up points up to 1 year after treatment start, were assessed with Form 90. Outcomes at follow‐up included consequences of drinking (Drinker Inventory of Consequences), quality of life (WHOQOL‐BREF), and DSM‐5 AUD symptoms (Mini International Neuropsychiatric Interview). Logistic regression and linear mixed models were used to examine the probability of maintaining risk‐level reductions at follow‐up and the association between risk‐level reductions and outcomes, respectively. Results: Reductions in risk levels were maintained over time (at least 1 level: OR 5.39, 95% CI 3.43, 8.47; at least 2 levels: OR 9.30, 95% CI 6.14, 14.07). Reductions were associated with reduced consequences of drinking and number of AUD symptoms, and minor, but statistically significant, improvements in quality of life. Conclusions: Maintaining reductions in WHO risk levels appears achievable for older adults seeking treatment for AUD. The small reduction of AUD symptoms and improvement of quality of life indicates that these reductions may not be adequate as the only treatment goal. Abstract : Data on treatment course of 963 60+ year‐old individuals suffering from Alcohol Use Disorder (AUD) in three countries (Denmark, Germany, and the US) showed that reductions in WHO drinking risk levels were stable over a one‐year follow‐up period. Reductions were associated with reduced consequences of drinking and number of DSM‐5 AUD symptoms. Maintaining reductions in WHO risk levels appear to be achievable for older adults with AUD and may be a feasible and stable outcome for treatment.